2020
DOI: 10.1016/j.brachy.2019.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Automated applicator digitization for high-dose-rate cervix brachytherapy using image thresholding and density-based clustering

Abstract: The purpose of the study was to develop and evaluate an automated digitization algorithm for high-dose-rate cervix brachytherapy, with the goal of reducing the duration of treatment planning, staff resources, variability, and potential for human error. METHODS: An automated digitization algorithm was developed and retrospectively evaluated using treatment planning data from 10 patients with cervix cancer who were treated with a titanium tandem and ovoids applicator set. Applicators were segmented, without huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 15 publications
3
17
0
Order By: Relevance
“…Deufel et al applied image thresholding and densitybased clustering in applicator digitization. Their HDs were ≤ 1.0 mm, and the differences for HR-CTV D 90% , D 95% , and OARs D 2cc were less or equal to 1% [12]. In the present study, the DSC was 0.89, HD was 1.66 mm, the dosimetric differences for the target were less than 0.30%, and the maximum 2.64% for OARs D 2cc .…”
Section: Discussionsupporting
confidence: 39%
See 2 more Smart Citations
“…Deufel et al applied image thresholding and densitybased clustering in applicator digitization. Their HDs were ≤ 1.0 mm, and the differences for HR-CTV D 90% , D 95% , and OARs D 2cc were less or equal to 1% [12]. In the present study, the DSC was 0.89, HD was 1.66 mm, the dosimetric differences for the target were less than 0.30%, and the maximum 2.64% for OARs D 2cc .…”
Section: Discussionsupporting
confidence: 39%
“…Before deep learning, researchers usually used threshold-based method to segment the applicator; however, this method still requires planners to define some points manually in clinical practice [5]. In recent years, more studies on automatic applicator reconstruction have been conducted based on deep learning [6][7][8][9][10][11][12].…”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation
“…92 The impact on dosimetric indices and DVHs (e.g., D2cc and D90, for OARs and targets, respectively) due to uncertainties in the applicator/needle reconstruction in 3D image-guided cervical BT has been well characterized by various investigators. [93][94][95][96][97] In general, the overall conclusion is that if the reconstruction error is within ±2 mm, the major dosimetric indices for both the target and OARs remain within 1-2%, on average, with variations of up to σ = 1-3% for individual cases, and with the magnitude being larger for OARs than targets.This is due to the geometric location of the OARs that generally are in higher dose gradient regions. Individual findings include Schindel et al, 93 who simulated the applicator shifts and concluded that to avoid a greater than 10% variation in the relevant dosimetric indices, the reconstruction uncertainty should be managed to be less than 3 mm.…”
Section: Applicator/needle Commissioning and Reconstructionmentioning
confidence: 97%
“…e purpose of image digitization is to convert continuous analog images into discrete digital images [17]. Sampling quantization or coding is usually used to convert the original continuous space and brightness into discrete space and brightness.…”
Section: Image Preprocessingmentioning
confidence: 99%